Mini Review Therapeutic Strategies Targeting for Biofilm and Bone Infections - Wu, Shizhou; Wu, Binjie; Liu, Yunjie; Deng, Shu; Lei, Lei; Zhang, Hui (Frontiers in Microbiology, 2022)
Bone infection results in a complex inflammatory response and bone destruction. A broad spectrum of bacterial species has been involved for jaw osteomyelitis, hematogenous osteomyelitis, vertebral osteomyelitis or diabetes mellitus, such as Staphylococcus aureus (S. aureus), coagulase-negative Staphylococcus species, and aerobic gram-negative bacilli. S. aureus is the major pathogenic bacterium for osteomyelitis, which results in a complex inflammatory response and bone destruction. Although various antibiotics have been applied for bone infection, the emergence of drug resistance and biofilm formation significantly decrease the effectiveness of those agents. The adhesion of biofilms to bone promotes bone destruction and protects bacteria from antimicrobial agent stress and host immune system infiltration. Moreover, bone is characterized by low permeability and reduced blood flow, further hindering the therapeutic effect for bone infections. Herein, we focus on biofilm and bone infection eradication with targeting therapeutic strategies. We summarize recent targeting moieties on biofilm and bone infection with peptide-, nucleic acid-, bacteriophage-, CaP- and turnover homeostasis-based strategies. The antibacterial and antibiofilm mechanisms of those therapeutic strategies include increasing antibacterial agents’ accumulation by bone specific affinity, specific recognition of phage-bacteria, inhibition biofilm formation in transcription level. As chronic inflammation induced by infection can trigger osteoclast activation and inhibit osteoblast functioning, we additionally expand the potential applications of turnover homeostasis-based therapeutic strategies on biofilm or infection related immunity homeostasis for host-bacteria. Based on this review, we expect to provide useful insights of targeting therapeutic efficacy for biofilm and bone infection eradication.